“FALTA DE DISPOSICIONES LEGALES SANCIONADORAS DE LA DEFENSORÍA DEL PUEBLO EN LO REFERENTE A LA LEY ORGÁNICA DE DEFENSA DEL CONSUMIDOR - GUERRERO TOLEDO, PABLO ANDRES (2016)
The Ombudsman's Office in Ecuador has established itself as the institution at the national level, call to protect and safeguard human rights, nature and the Ecuadorian and Ecuadorians. Also participates in the control of the organizations and agencies of the sector public and private individuals. The principles on which is based the Office of the Ombudsman are independence, accessibility, flexibility, credibility, but also the gratuity, informality and immediacy, applying the resources and procedures that lead to the protection of the human rights of the citizens in the Ecuador. A specific competence on which I conducted this study is the defence of the rights of the consumer. In its acting this entity has to preserve independence and autonomy to act only in the defense of the citizens. In our country rights and sanctions for violations of consumer were controlled by trade or law of intellectual property, after a long process in our country, is emphasize that even the rights of consumers in the Ecuador, are now elevated to the status of constitutional guarantee, and are enforced by any judge, court or competent authority. According to offence in our law of defence to the consumer, and contemplated in the new Constitution of the Republic of the Ecuador, we can highlight the following rights of consumers: protection of life, health and safety in consumption, as well as the satisfaction of fundamental needs and access to basic services; Freedom of choice; To receive optimal quality basic services; To receive accurate, clear, timely, and complete information about good and service, as well as the conditions of purchase, price, and quality; The protection of abusive or misleading advertising; To follow the legal and judicial actions that correspond. In accordance with the enshrined in the law of consumer, corresponds to the Ombudsman: "defend and exciting, ex officio or upon request of a party, where appropriate, the enforcement of individual and collective fundamental rights that the 5 Constitution of the Republic, laws, agreements and international treaties ratified by the Ecuador guarantee. The Ombudsman can start and continue ex officio, or at the request of a party, the necessary investigations to clarify the facts that reporting and that comes from the public sector or from individuals; "they are responsible to know and meet over violations of the norms contained in this law as we see the Ombudsman has no punitive powers to defend the rights of the consumer, to punish and to know these sanctions are the judges of first instance, the judge of contraventions of the respective jurisdiction, and, in case of appeal, judge of Assize of the respective jurisdiction". Analysis to the right of access to justice, we have observed that there are major flaws in the institution of the Ombudsman who does not promote or defend the rights of the consumer in the Ecuador, this institution is responsible for as stipulated in the Constitution of the Republic, therefore the Ombudsman have not contributed to the citizenship with new proposals to improve the procedure which is established law of Defense to the consumer so the system of access to justice in matters of consumption is weakened, and therefore has slowed the credibility of this institution and increased abuse and infringement of the rights of consumers